Absence or low IGF‐1R‐expression in esophageal adenocarcinoma is associated with tumor invasiveness and radicality of surgical resection. Issue 8 (16th June 2015) - De Bruijn, Kirstin; Biermann, Katharina; Shapiro, Joel; Dogan, Fadime; Spaander, Manon; Janssen, Joseph; Wijnhoven, Bas; Borsboom, Gerard; Hofland, Leo; van Eijck, Casper
<x xml:space="preserve">Abstract</x> Background and Objectives Esophageal adenocarcinoma (EAC) incidence increases, maybe due to increasing prevalences of obesity and diabetes. Concurrent hyperinsulinemia might promote carcinogenesis via the insulin‐like growth factor‐I receptor (IGF‐1R). Expression of the IGF‐1R was studied in correlation with diabetes and prognostic parameters. Methods Patients with EAC undergoing esophagectomy were prospectively selected. From resected tumors a tissue microarray was constructed. Immunohistochemistry evaluated IGF‐1R‐expression. Logistic‐, cox regression models and survival analyses assessed if diabetes and IGF‐1R‐expression were associated with prognostic parameters. IGF‐1R‐expression in normal and Barrett tissues was studied. Results Absence or low IGF‐1R‐expression was associated with T3‐, grade 3 tumors and R1 resections (P = 0.001, P = 0.025, P < 0.001, respectively). Logistic regression showed that this was associated with R1 resections (HR 0.24, 95%CI 0.11–0.52). Diabetes was not associated with IGF‐1R‐expression (P = 0.612). Absence or low IGF‐1R‐expression decreased 5‐year overall survival (P = 0.023) univariably, but not multivariably. IGF‐1R‐expression was present in Barrett tissues, but diminished in high‐grade dysplasia. Conclusions Absence or low expression of IGF‐1R was associated with high grade‐ and advanced tumors and less radical resections. IGF‐1R might be a tumor marker in Barrett's esophagus since a change in expression patterns was found in the course from normal esophageal tissue to adenocarcinoma. J. Surg. Oncol. 2015 111:1047–1053. © 2015 Wiley Periodicals, Inc.